The Development of Inclusive Practice in the Contex of COVID – 19 Pandemic: the overcoming learning difficulties of students having special educational needs - Miltenienė, Lina; Melienė, Rita; Galkienė, Alvyra; Rutkienė, Aušra (Pedagogika, 2023)
The transition to emergency distance education in the context of the COVID-19 pandemic has had a significant negative impact on children with special educational needs. The article presents a study conducted in Lithuania. The aim of the study was to reveal the practice of inclusive education and its development in the context of the COVID-19 pandemic in terms of the difficulties of students having SEN (special educational needs) and overcoming strategies based on the experience of schools. The following problematic questions were formulated: What learning difficulties and barriers did students with SEN and their educators face in the context of COVID-19? What are methods used to overcome the difficulties? The research data were collected using the focus group method. There were organized 18 focus group discussions. The focus groups consisted of teachers of various pedagogical specializations (teachers of various subjects, support specialists – social pedagogues, special pedagogues, speech therapists), psychologists and representatives of school administrations (principals, deputies, heads of departments) (N = 173). The research disclosed that students with SEN were more vulnerable in the context of distance learning due to their individual educational needs, their learning process is hampered by educational barriers and a lack of support at school and at home. An effective school support system, teamwork and collaboration, teacher support and working in small groups help to achieve better results and overcome difficulties.